e3*x | ||
a) ∫ | ||
1+e6*x |
1 | ||
dt= | e3*xdx | |
3 |
dt | |
=e3*x | |
3 |
dt | 1 | 1 | dt | |||||
∫ | * | = | ∫ | <−wzór elementarny | ||||
3 | 1+t2 | 3 | 1+t2 |
dx | ||
b) ∫ | ||
√ex+1 |
2tdt | 2tdt | ||
=dx | dx = | |||
ex | 1−t2 |
| 2tdt | 1 | tdt | |||||||||||
∫ | = ∫ | * | = ∫ | |||||||||||
t | 1−t2 | t | 1−t2 |
du | ||
− | =tdt | |
2 |
| du | du | 1 | 1 | du | 1 | ||||||||||||||
∫ | = ∫ − | {u} = − ∫ | * | = − | ∫ | = − | ||||||||||||||
u | 2 | 2 | u | 2 | u | 2 |
1 | 1 | |||
− | ln|1−t2| = − | ln|1−ex+1| | ||
2 | 2 |
e−4*x | ||
c) ∫ | ||
√4+e−4*x |
1 | ||
2tdt=− | * e−4*xdx / *−4 | |
4 |
tdt | ||
∫ U {−8tdt}{t} = −8 ∫ | = −8 ∫ dt = −8 *t = −8 * √4+e−4*x | |
t |
sin3 x | ||
d) ∫ | a tą jak przez podstawianie czy czesci ? | |
cos4 x |
sin(x) | 1 | sin2(x) | 2 | sin(x)cos(x) | |||||
∫sin2(x) | dx= | − | ∫ | dx | |||||
cos4(x) | 3 | cos3(x) | 3 | cos3(x) |
sin3(x) | 1 | sin2(x) | 2 | sin(x) | |||||
∫ | dx= | − | ∫ | dx | |||||
cos4(x) | 3 | cos3(x) | 3 | cos2(x) |
sin3(x) | 1 | sin2(x) | 2 | 1 | ||||
∫ | dx= | − | +C | |||||
cos4(x) | 3 | cos3(x) | 3 | cos(x) |